2006
DOI: 10.1371/journal.pone.0000111
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between PolyQ and Protein Context Delays Aggregation by Forming a Reservoir of Protofibrils

Abstract: Polyglutamine (polyQ) diseases are inherited neurodegenerative disorders caused by the expansion of CAG codon repeats, which code for polyQ in the corresponding gene products. These diseases are associated with the presence of amyloid-like protein aggregates, induced by polyQ expansion. It has been suggested that the soluble aggregates rather than the mature fibrillar aggregates are the toxic species, and that the aggregation properties of polyQ can be strongly modulated by the surrounding protein context. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
55
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 38 publications
7
55
2
Order By: Relevance
“…Thus, the role of the polyQ stretch in the structure of the aggregate core ranges from peripheral in the early spherical detergent-soluble prefibrillar species to central in the second stage, the formation of detergent-resistant fibrils. Strikingly, our results on in-cell aggregation of this polyQ-containing chimeric system are entirely analogous to those observed for ataxin-3 in vitro in the Bottomley laboratory (22,23) and for a chimera of glutathione S-transferase and exon 1 of huntingtin (17). This emphasizes the potential general significance of the effect of polyQ segments on their neighboring domains and the resulting impact on the time-dependent character of aggregates and suggests that the complex aggregation mechanisms previously observed in vitro can also occur in the cellular environment.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Thus, the role of the polyQ stretch in the structure of the aggregate core ranges from peripheral in the early spherical detergent-soluble prefibrillar species to central in the second stage, the formation of detergent-resistant fibrils. Strikingly, our results on in-cell aggregation of this polyQ-containing chimeric system are entirely analogous to those observed for ataxin-3 in vitro in the Bottomley laboratory (22,23) and for a chimera of glutathione S-transferase and exon 1 of huntingtin (17). This emphasizes the potential general significance of the effect of polyQ segments on their neighboring domains and the resulting impact on the time-dependent character of aggregates and suggests that the complex aggregation mechanisms previously observed in vitro can also occur in the cellular environment.…”
supporting
confidence: 83%
“…In contrast, studies on full-length Htt exon 1 fragments have identified non-amyloid aggregates (5-7) in addition to mature amyloid. Moreover, studies of natural multidomain polyQ-containing proteins (22,23), as well as an artificial chimera like the one studied here (17), also reveal multistage aggregation with early prefibrillar species. In particular, the extensive recent studies of ataxin-3 aggregation in vitro have established that this multidomain protein follows a two-stage aggregation process with the first step dominated by the Josephin domain, and not the polyQ-rich domain (18,22,23).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Flanking sequences directly adjacent to the poly(Q) domain within htt strongly influence aggregation (8,9). The first 17 amino acids of htt exon1 (Nt17) has been shown to promote oligomer formation in synthetic poly(Q) peptides (10,11), and targeting the Nt17 domain is an effective way of altering the aggregates formed and the kinetics of formation (10,12).…”
mentioning
confidence: 99%